20. CURRENT KNOWLEDGE AND PRACTICE ON FOOD SAFETY AMONG FOOD PROCESSORS AT RESTAURANTS IN PHU MY DISTRICT, BINH DINH PROVINCE IN 2023 AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2023)
Objective: Describe the current knowledge and practices on food safety among restaurant food processors and some related factors in Phu My district, Binh Dinh province in 2023.Subject and method: Cross-sectional descriptive study, combining quantitative and qualitative on all 284 food processors at 284 restaurants in Phu My district, Binh Dinh province, in 2023 in order to evaluate knowledge, practice on food safety and some related factors. We were collecting data based on a questionnaire of knowledge and practice checklist of 16 criteria and in-depth interviews with 9 people involving food safety management.Results: The percentage of food processors with food safety knowledge was 73.6% and the food safety practice reached 61.3%. Some factors related to knowledge of processors on food safety include education level of the processor (OR=3.6; 95% CI: 1.9 - 6.6); time working at a restaurant (OR= 2.2; CI 95%: 1.2 – 4.0); food processing experience (OR= 5.9; CI 95%: 1.5 – 22.6); organize training on food safety (OR=2.4; CI 95%: 1.1 – 5.6); conducted communication on food safety (OR=2.3; CI 95%: 11.2 – 4.2); Some factors related to practices of processors on food safety include: education level of the processors (OR=2.3; 95% CI: 1.2 - 4.4 ); Frequency of performing inspection and supervision on food safety in 1 year (OR= 2.2; 95% CI: 1.2 - 4.1).Conclusion: The food safety knowledge and practice of food processors at restaurants is relatively high but It has not met the requirements of the socio-economic development of our country. Some factors such as education, time about food processing and work experience at the restaurant; be trained and communicated related to food safety knowledge of processors. Besides education, the frequency of inspection and supervision for 1 year is related to food safety practice of food processors.
Keywords: Food processors; knowledge, practice, food safety.